Comments on 'High-dimensional model representation for structural reliability analysis' by R. Chowdhury, B. N. Rao and A. M. Prasad, Communications in Numerical Methods in Engineering 2009; 25:301-337 - Rahman, S.; Xu, H. (International journal for numerical methods in biomedical engineering, 2011)
The authors of the paper published in Commun. Numer. Methods Eng. (2009; 25:301–337) have claimed to present a new computational tool entailing high‐dimensional model representation for structural reliability analysis. This letter demonstrates that the underlying reliability method already exists and was originally developed in the Xu and Rahman paper, published in Probabilist. Eng. Mech. (2005; 20:239–250). The authors do not acknowledge the contribution of Xu and Rahman and convey the impression that they are developing the method for the very first time. Instead, the authors have reinvented the wheel. Copyright © 2010 John Wiley & Sons, Ltd.